Analisis Pengaruh Simpanan Pokok Simpanan Wajib Dan Simpanan Sukarela Terhadap Sisa Hasil Usaha Anggota Di Koperasi Serba Usaha Talenta Kalabahi Kabupaten Alor - Sailana, Aprilia Sarlin; Maro, Yustina; Tang, Sefnat Aristarkus; Sabu, Junius Menase Sau (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the effect of Principal Savings, Compulsory Savings, Voluntary Savings on the Remaining Results of Business at the Talent Multi-Business Cooperative, Alor Regency. The problem of this research is whether there is a simultaneous effect of principal savings, mandatory savings, voluntary savings on SHU. The population in this study is the financial statements for the last 5 years 2018-2023. And the sample is all data regarding principal savings, mandatory savings, voluntary savings and Remaining Profits from 2018-2022. This type of research is quantitative research using secondary data. data collection was carried out by interviews, documentation studies, and literature studies. The statistical method used in this study is multiple linear regression with the significance of the t test and the significance of the F test as a benchmark for taking the hypothesis. The results of the study show that partially principal savings affect the remaining business results in the Talenta Kalabahi Multi-business Cooperative, Alor Regency. With a significance value of t of 0.003. Partially, the obligatory saving has an effect on the remaining results of operations in the Talenta Kalabahi Multi-business Cooperative, Alor Regency. Which is marked by a significance value of the t test of 0.00, partially voluntary savings have no effect on the remaining results of operations in the Talenta Kalabahi Cooperative, Alor Regency. Which is marked by a significance value of the t test of 0.796. And simultaneously principal savings, mandatory savings, voluntary savings affect the remaining business results in the Talenta Kalabahi Cooperative, Alor Regency. Which is marked with a significance value of the F test of 0.00.